Incidence of Pneumonia and Predictors Among Human Immunodeficiency Virus Infected Children at Public Health Institutions in the Northwest Part of Ethiopia: Multicenter Retrospective Follow-Up Study - Mengesha T; Embiale T; Azmeraw M; Kerebeh G; Mulatu S; Meseret F; Birhanu M (Dove Medical Press, 2022)
Teshale Mengesha,1 Tsegasew Embiale,1 Molla Azmeraw,2 Gashaw Kerebeh,3 Sileshi Mulatu,4 Fentahun Meseret,5 Minyichil Birhanu4 1Department of Pediatrics and Child Health Nursing, College of Medicine and Health Sciences, Dire Dawa University, Dire Dawa, Ethiopia; 2Department of Nursing, College of Health Sciences, Woldia University, Woldia, Ethiopia; 3Department of Pediatrics and Child Health Nursing, College of Medicine and Health Sciences, Debre Tabor University, Debre Tabor, Ethiopia; 4Department of Pediatrics and Child Health Nursing, School of health Sciences, College of Medicine and Health Sciences, Bahir Dar University, Bahir Dar, Ethiopia; 5Department of Pediatrics and Child Health Nursing, School of Nursing and Midwifery, College of Health and Medical Sciences, Haramaya University, Harar, EthiopiaCorrespondence: Teshale Mengesha, Pediatrics and Child Health Nursing at Dire Dawa University, Dire Dawa, Ethiopia, Email mengeteshu12@gmail.comIntroduction: Pneumonia is an inflammation of the lung parenchymal structure secondary to hematogens spread of pathogens, inhalation, or aspiration. It is also one of the most frequently occurring opportunistic infections in HIV-infected children. In Ethiopia, data on the incidence and predictors of opportunistic infection, especially pneumonia, among HIV-infected children is very limited. Hence, this study aimed to assess the incidence of pneumonia and predictors among HIV-infected children at public health institutions in the Northwest part of Ethiopia.Methods: An institution-based retrospective cohort study was conducted among 342 HIV-infected children at public health institutions from January 1, 2013 to December 30, 2020. Log rank test was used to compare the survival curves between different explanatory variables. Bivariable Cox proportional hazards regression model was employed for each explanatory variable to check the association with the outcome variable. Variables found to have a p-value of < 0.25 in the bivariable analysis were candidates for the multi-variable proportional hazard model. Cox proportional hazards model was used at 5% level of significance to identify predictors of pneumonia.Results: This study included 342 records of HIV-infected children who started antiretroviral therapy between the periods of January 1, 2013 to December 30, 2020. The overall incidence rate of pneumonia during the follow-up time was 5.57 (95% CI: 4.4, 7.0) per 100 child-years of observation. Those children who did not take cotrimoxazole preventive therapy (AHR: 3, 95% CI: 1.40, 6.44), being underweight at baseline (AHR: 2.6, 95% CI: 1.41, 4.86), having baseline advanced disease (clinical stages III and IV) (AHR: 2.8, 95% CI: 1.30, 6.04), and presenting with recently detected viral load (AHR: 5.9, 95% CI: 2.53, 14.06), were more likely to develop pneumonia.Conclusion: Pneumonia incidence rate was high. Providing prophylaxis and nutritional supplementation for those children with baseline advanced disease stage, low weight for age and detectable viral load would reduce pneumonia occurrence.Keywords: pneumonia, incidence, HIV, children, Ethiopia